ENHANCING ESP STUDENTS' CREATIVE THINKING SKILLS THROUGH VIDEO ADVERTISING PROJECTS: A CASE STUDY IN ENGLISH FOR TOUR OPERATIONS - Chaerunnisah, Indah Utami; Nova, Muhamad (Premise: Journal of English Education and Applied Linguistics, 2025)
The rapid growth of global business in the 21st century necessitates integrating creative thinking skills into teaching and learning programs. Regarding this issue, one potential learning output for integrating creative thinking skill enhancement in teaching and learning activities is the creation of video advertisements. The current study investigated the students' perspective toward video advertising project implementation to enhance students' creative thinking skills in a project-based learning class. The current study is a case study that took 24 students as participants. The video project was conducted through 4 meetings. In the current study, the data were obtained through observation, a questionnaire, and an interview. The data was then analyzed using qualitative data analysis, which involved data reduction, data display, and conclusion drawing. The study's results indicate that all students recognized the video advertising project's potential to positively impact their creativity, particularly in terms of enforcing creative ideas, developing scriptwriting skills, refining video editing skills, and honing negotiation skills. Only a few students perceived it negatively, as they faced challenges in group contributions. Thus, implementing a video advertising project is necessary to improve students' creative thinking skills.